TL/OSL properties of natural schist for archaeological dating and retrospective dosimetry - Afouxenidis, D.; Stefanaki, E.C.; Polymeris, G.S.; Sakalis, A.; Tsirliganis, N.C.; Kitis, G. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2007)
Schist, a metamorphic rock composed largely of quartz and muscovite, has been used as a building stone through the centuries in many parts of the world. In ancient Greece, it was used in buildings and monuments (Knossos, Karthaia, etc). Basic TL and OSL properties of schist are studied in the present work to evaluate its potential use in archaeological dating and retrospective dosimetry. In particular, the optical stability, as well as the linearity of the TL and OSL signal were investigated for samples of natural schist obtained from a roofing slate. The results indicate that both signals are rapidly bleached when the sample is exposed to sunlight. An exposure of 1 min reduces the TL signal by 93%, the IRSL signal by 99% and the post-IR BSL signal by 90%. The dose response was found to be linear for a radiation dose at least up to 75 Gy for the TL and the IR OSL signal and at least up to 25 Gy for the post-IR BSL signal.